Enhancing the wear resistance of Ti6Al4V by laser surface texturing - Mohd Harizan, Zul; Mahadzir, Ishak@Muhammad; R. M., Nasir; Aiman, Mohd Halil; Quazi, Moinuddin Mohammed (Trans Tech Publications Ltd, 2025)
This study examines the wear behavior of Ti6Al4V following nanosecond pulse laser surface texturing (LST) using 15 W power, 60 kHz frequency, and 180 mm/s speed. Tested under dry sliding conditions with a 20 N load, 0.3 m/s speed, and 900 s duration, LST produced melt bulges that enhanced surface wear resistance. This study demonstrates that nanosecond pulse laser surface texturing on Ti6Al4V significantly enhances wear resistance, reducing wear rate by 3% and coefficient of friction by 5%.